Aplikasi Edukasi Awal Mula Penjajahan Belanda Di Indonesia Berbasis Mobile - Filia Sekar Murty; Ionia Veritawati; Febri Maspiyanti (Journal of Informatics and Advanced Computing (JIAC), 2022)
The learning process on Indonesian history did not attract the attention of students, nor did there escape rumors about the abolition of teaching history material in schools in the future curriculum. Junior high school teachers have made various efforts to deliver history lessons, ranging from inviting students to visit historical places, and making activities in class to making theater with a historical theme to commemorate important days. Therefore, in this study, the author develops an educational application in history subjects, more precisely in the history of the early arrival of the Dutch to Indonesia using the Unity software. This study uses the waterfall method so that the process is faster with good results, and uses the collection of application evaluations that are generated online using the validity and reliability method for students from junior high and high school levels. Based on the results of the evaluation of users of educational applications that have been made, the reliability and validation values of the questions and content provided can be stated as strong based on the significance table.